Posttraumatic Stress and Posttraumatic Growth Among Low-Income Mothers who Survived Hurricane Katrina - Lowe, Sarah R. (2013)
OBJECTIVE: The purpose of the study was to explore the relationship between posttraumatic stress (PTS) and posttraumatic growth (PTG) after Hurricane Katrina, and the role of demographics, pre-disaster psychological distress, hurricane-related stressors, and psychological resources (optimism and purpose) in predicting each. METHOD: Participants were 334 low-income mothers (82.0% non-Hispanic Black) living in the New Orleans area prior to Hurricane Katrina, who completed surveys in the year prior to the hurricane (T1), and one and three years thereafter (T2 and T3). RESULTS: Higher T2 and T3 PTS full-scale and symptom cluster subscales (intrusion, avoidance, and hyperarousal) were significantly associated with higher T3 PTG, and participants who surpassed the clinical cut-off for probable PTSD at both T2 and T3 had significantly higher PTG than those who never surpassed the clinical cut-off. Older and non-Hispanic Black participants, as well as those who experienced a greater number of hurricane-related stressors and bereavement, reported significantly greater T3 PTS and PTG. Participants with lower T2 optimism reported significantly greater T3 intrusive symptoms, whereas those with higher T1 and T2 purpose reported significantly greater T3 PTG. CONCLUSIONS: Based on the results, we suggest practices and policies that identify disaster survivors at greater risk for PTS, as well as longitudinal investigations of reciprocal and mediational relationships between psychological resources, PTS, and PTG.